Genome-Wide Identification of CircRNAs of Infective Larvae and Adult Worms of Parasitic Nematode, Haemonchus contortus - Zhou, Caixian; Zhang, Yao; Wu, Simin; Wang, Zhiheng; Tuersong, Waresi; Wang, Chunqun; Liu, Feng; Hu, Min (Frontiers in Cellular and Infection Microbiology, 2021)
CircRNAs, a novel class of ncRNA family, are endogenous transcriptional products involved in various biological and physiological processes in plants and animals. However, almost no information is available for circRNAs of parasitic helminths. In the present study, the circRNAs repertoire was comprehensively explored in Haemonchus contortus, a blood-sucking parasitic nematode of ruminants. In total, 20073 circRNAs were identified and annotated from three key developmental stages/genders of H. contortus including the free-living infective third-stage larvae (L3, 18883), parasitic adult female (Af, 3491), and male worms (Am, 2550) via deep-sequencing technology and bioinformatic analysis. Among these identified circRNAs, 71% were derived from exonic regions of protein-coding genes. The number of circRNAs transcribed from the X chromosome (4704) was higher than that from Chromosome I-V (3143, 3273, 3041, 3030, 2882). The amount of highly expressed circRNAs in third-stage larvae was significantly more abundant than that in adult stage. 15948 and 16847 circRNAs were differentially expressed between Af and L3s and between Am and L3, respectively. Among them, 13409 circRNAs existed in both comparisons. Furthermore, 1119 circRNAs were differentially expressed between Af_and_Am. GO enrichment analysis indicated that source genes of circRNAs differentially expressed between Am and L3 as well as between Af and L3 were significantly enriched in many biological processes, primarily including signaling, signal transduction and cell communication terms. KEGG analysis revealed that parental genes of differentially expressed circRNAs were mainly related to metabolism (pyruvate metabolism, glycerophospholipid metabolism, and carbon metabolism), MAPK signaling pathway, and phosphatidylinositol signaling system. Moreover, many circRNAs contained one or more miRNA potential binding sites, suggesting that they could regulate gene expression at the post-transcriptional level. Furthermore, the correctness of head-to-tail back splicing site and alternative circularization events were verified by Sanger sequencing using both divergent and convergent primers. Finally, the reliability of RNA-Seq data and the resistance of circRNAs to RNase R digestion were confirmed by quantitative RT-PCR. Taken together, our findings provide a foundation for elucidating the regulatory mechanisms of circRNAs in H. contortus, which will advance the understanding of circRNAs in parasitic nematodes.